2016
DOI: 10.4269/ajtmh.15-0620
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hepatic Cystic Echinococcosis in Patients from the Southeastern Rhodope Region of Bulgaria in 2004–2013: Comparison of Current Practices with Expert Recommendations

Abstract: Abstract. Cystic echinococcosis (CE) is a clinically complex chronic parasitic disease, management options for which include surgery, percutaneous treatments, and treatment with albendazole (ABZ) for active cysts, and the "Watch-andWait" approach for uncomplicated, inactive cysts. We examined, retrospectively, the clinical management of 334 patients with hepatic CE from the southeastern Rhodope region of Bulgaria between 2004 and 2013. Cysts were reclassified according to the World Health Organization Informal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Introducing PT into Mongolia should be considered because it carries less risks for the patients, reduces treatment cost and length of hospital stay. A study in Bulgaria showed similar deviations from best practices as recommended by WHO-IWGE expert consensus[ 43 ].…”
Section: Discussionmentioning
confidence: 94%
“…Introducing PT into Mongolia should be considered because it carries less risks for the patients, reduces treatment cost and length of hospital stay. A study in Bulgaria showed similar deviations from best practices as recommended by WHO-IWGE expert consensus[ 43 ].…”
Section: Discussionmentioning
confidence: 94%
“…According to the results of previous studies, the therapeutic effect of different drugs on hydatid disease decreases when the cysts are larger. [ 5 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options for hydatid disease include surgery, medical therapy, and PAIR (Puncture, Aspiration, Injection of scolicidal agent, Reaspiration), whereas the clinically silent and inactive cysts are commonly monitored by “Watch-and-Wait” approach. [ 3 5 ] Medical therapy may be the only treatment option for multiple, very small or inaccessible cysts and in old people as well as in those who do not accept surgery. Medical therapy may also be applied before surgery to reduce the cyst size and to decrease the recurrence rate after surgical operation.…”
Section: Introductionmentioning
confidence: 99%
“…Human infection usually occurs after ingestion of infective eggs passed in the feces from dogs via direct contact or through environmental contamination . CE is a chronic disease with complex nature and may be asymptomatic, severe or even a fatal infection in human beings . One hydatid cyst may grow as much as a cyst containing several liters of hydatid fluid …”
Section: Introductionmentioning
confidence: 99%